2012
DOI: 10.1161/circimaging.112.976167
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for Neoatherosclerosis

Abstract: Optical coherence tomography (OCT) is an emerging intracoronary diagnostic modality that provides high-resolution images of coronary artery in vivo. 11 In addition to tissue characterization in native coronary plaques, OCT has been applied to characterize neointima after stent implantation. 12 Indeed, several OCT studies revealed the development of lipid-laden neointima inside the stents, and OCT has become the modality of choice to study atherosclerotic change of neointima. 7,9,10 Background-Recent studies ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(78 citation statements)
references
References 39 publications
6
69
1
2
Order By: Relevance
“…Neoatherosclerosis is less frequent in BMS as compared with DES, so that the drug released from the latter seems to be one of the causative factors due to the incomplete endothelialization related to the drug itself (43,44).…”
Section: Neoatherosclerosismentioning
confidence: 99%
“…Neoatherosclerosis is less frequent in BMS as compared with DES, so that the drug released from the latter seems to be one of the causative factors due to the incomplete endothelialization related to the drug itself (43,44).…”
Section: Neoatherosclerosismentioning
confidence: 99%
“…In light of the relatively well‐preserved vascular structure and less severe luminal narrowing,1, 2, 9 it is conceivable that ACS caused by PE without significant luminal narrowing may be stabilized by effective antithrombotic treatment without stent implantation. This conservative strategy would avoid both early (vessel dissection, distal embolism, and acute stent thrombosis) and late (restenosis, neoatherosclerosis, and late and very late stent thrombosis) complications of stent implantation 10, 11, 12, 13, 14. Indeed, few reports with a small number of cases have suggested that a subset of patients with ST‐segment elevation myocardial infarction caused by PE might be treated by antithrombotic therapy with favorable outcome 2, 15, 16.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several clinical factors have been reported as predictors of NA including, stent duration, smoking, CKD, DES use, and angiotensin converting enzyme inhibitor/angiotensin II receptor blocker use. [9][10][11] However, these predictive factors…”
Section: Discussionmentioning
confidence: 99%
“…6,7) The development of optical coherence tomography (OCT) has enabled us to identify in-stent NA, which is characterized by vulnerable plaque features such as lipid laden plaque, thin-cap fibroatheromas (TCFA), and luminal thrombus and therefore, patients with NA have often unstable coronary disease. 8) Previous reports have suggested that elapsed time after stent implantation, smoking, and chronic kidney disease (CKD) are predictors of NA after stent implanatation, [9][10][11] however, the precise mechanism of NA has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%